2019
DOI: 10.2196/15466
|View full text |Cite
|
Sign up to set email alerts
|

Understanding End-User Perspectives of Mobile Pulmonary Rehabilitation (mPR): Cross-Sectional Survey and Interviews

Abstract: Background Pulmonary rehabilitation (PR) is an effective intervention for the management of people with chronic respiratory diseases, but the uptake of and adherence to PR programs is low. There is potential for mobile health (mHealth) to provide an alternative modality for the delivery of PR, overcoming many of the barriers contributing to poor attendance to current services. Objective The objective of this study was to understand the needs, preference… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…In any case, when developing mHealth tools, it is important to consider factors such as age, information technology experience, education level, and possible comorbidities. Engagement with patients in the design and testing is essential to make sure the intervention is easy for older people [ 38 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In any case, when developing mHealth tools, it is important to consider factors such as age, information technology experience, education level, and possible comorbidities. Engagement with patients in the design and testing is essential to make sure the intervention is easy for older people [ 38 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of this program followed the mHealth Development and Evaluation framework (Whittaker et al, 2012), which provides a process to guide the development and testing of mHealth interventions with a focus on implementation, behavioral change theory, and involvement of the target population. The development of the content was informed by a review of current PR program content, literature, existing mHealth interventions, patient resources, and our formative research with the target audience (Dobson et al, 2019a). The program was informed by behavior change theories and incorporates behavior change techniques (BCTs) (Michie et al, 2013) including information about health consequences, social support, (practical) instructions on how to perform the behavior, and graded tasks.…”
Section: Interventionmentioning
confidence: 99%
“…This project aims to develop a mobile phone-based PR support program using the steps outlined in the mHealth Development and Evaluation Framework (Whittaker et al, 2012). Formative work undertaken for this project found high interest in mPR from both patients and healthcare professionals (Dobson et al, 2019a). Both patients and healthcare professionals identified potential for an mPR program to overcome current barriers to traditional PR programs but had concerns regarding technology and the lack of a group environment within a digital program.…”
Section: Introductionmentioning
confidence: 99%
“…A mixed-methods (survey and interview) study undertaken for this project found high interest in mPR from both patients and healthcare professionals [7]. While participants saw the potential to improve access to PR through technology, there was concern about access to technology and digital literacy, as well as patient safety and the lack of group environment (as compared to gold standard PR).…”
Section: Original Mpr Design Intervention and Pilot Field Testmentioning
confidence: 99%